Long-term humoral immunogenicity, safety and protective efficacy of inactivated vaccine against reindeer rabies - Matveeva, Irina; Karpova, Olga; Nikitin, Nikolai; Akilin, Oleg; Yelnikov, Vasiliy; Litenkova, Irina; Melnik, Roman; Melnik, Nikolai; Asimov, Karim; Zaberezhny, Aleksey; Fyodorov, Yriy; Markova, Evgeniya (Frontiers in Microbiology, 2022)
The core element of the reindeer rabies eradication strategy is regular application of vaccines to obtain and uphold a vaccination coverage sufficient for the ceasing of rabies virus transmission. This article presents the results of reindeer humoral immunity intensity and duration study after the immunization with two form of inactivated rabies vaccines (adjuvanted liquid vaccine and non-adjuvanted lyophilized vaccine) based on the Shchelkovo-51 rabies virus strain. Efficiency of post-vaccine immunity was assessed by measuring the animal blood serum virus-neutralizing antibody level in a neutralization test. The study determined the efficient rabies vaccine injection dose as equal to 3 ml. A single dose of 3 ml of these vaccines induced stable production of specific neutralizing antibodies in reindeer as early as 7 day after administration, and by 30 days after immunization, it significantly exceeded the minimal threshold level accepted by OIE. Two doses of vaccines administration with an interval of 30 days are required to achieve a strong immunity with the rabies-specific virus-neutralizing antibody titer of more than 0.5 IU/ml for at least 2 years. Our data do not support the benefit of an adjuvanted vaccine for the prevention of rabies in reindeer.